2022
DOI: 10.1007/s12149-022-01716-w
|View full text |Cite
|
Sign up to set email alerts
|

Opportunistic skeletal muscle metrics as prognostic tools in metastatic castration-resistant prostate cancer patients candidates to receive Radium-223

Abstract: Objective Androgen deprivation therapy alters body composition promoting a significant loss in skeletal muscle (SM) mass through inflammation and oxidative damage. We verified whether SM anthropometric composition and metabolism are associated with unfavourable overall survival (OS) in a retrospective cohort of metastatic castration-resistant prostate cancer (mCRPC) patients submitted to 18F-Fluorodeoxyglucose Positron Emission Tomography/Computed Tomography (FDG PET/CT) imaging before receiving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…Previous studies in men with PC have assessed sarcopenia based on CT scans using the entire cross-sectional skeletal muscle area at the level of the 3 rd lumbar vertebra, or of the psoas muscle [ 8 12 , 30 ]. Although this opportunistic method provides accurate estimates of muscle mass and density, it omits other important elements of sarcopenia, such as measures of muscle function that have been included in the updated definition per expert study groups on sarcopenia [ 2 , 14 , 19 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies in men with PC have assessed sarcopenia based on CT scans using the entire cross-sectional skeletal muscle area at the level of the 3 rd lumbar vertebra, or of the psoas muscle [ 8 12 , 30 ]. Although this opportunistic method provides accurate estimates of muscle mass and density, it omits other important elements of sarcopenia, such as measures of muscle function that have been included in the updated definition per expert study groups on sarcopenia [ 2 , 14 , 19 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies in men with mCRPC have demonstrated that CT-based low skeletal muscle quantity/mass or muscle quality at the level of the 3 rd lumbar vertebra, notably also of the psoas muscle, are associated with a higher risk of grade I-II neutropenia during chemotherapy [ 8 ], disease progression [ 9 , 10 ], and overall mortality [ 9 , 11 , 12 ]. Although these studies provided promising evidence of the role of sarcopenia in predicting clinical and disease outcomes in men with mCRPC, there was no consensus on the skeletal muscle measure (e.g., mass versus quality) that could best predict outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Beyond the enrollment procedure for 223 RaCl 2 therapy, a simple count of the number of bone metastases turns out to be extremely reductive. Indeed, a number of studies focused on the use of imaging semi-quantification as a tool to assess tumor spread in mCRPC candidates to receive 223 RaCl 2 therapy [ 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. The BSI, a measure expressing the fraction of the skeleton involved by the tumor as a percentage value of the whole body mass [ 14 ], has been proposed for determining the extent of disease, monitoring disease progression, and assessing treatment response in different malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…In a precision medicine perspective, the addition of molecular biomarkers to the BIO-Ra score might further improve its capability for selecting the best drug for the right patient. A similar consideration applies to next-generation imaging, particularly with positron emission tomography (PET), whose functional nature may at the same time provide an accurate staging of the disease extent [ 30 ] and display tumour heterogeneity in vivo [ 13 , 17 , 18 , 31 , 32 , 33 , 34 , 35 ], potentially improving the patient selection process. Unfortunately, given the study’s retrospective nature, we built the BIO-Ra score exclusively using widely available clinical and lab data.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies previously investigated many parameters potentially able to improve patient’s selection since baseline [ 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. However, most of them remained inconclusive since none of the identified clinical or biochemical biomarkers has been validated as a unique and reliable selection tool.…”
Section: Introductionmentioning
confidence: 99%